Linear and nonlinear FE analyses of a container vessel in harsh sea state - Ringsberg, Jonas; Li, Zhiyuan; Tesanovic, Andrea; Knifsund, Camilla (Ships and Offshore Structures, 2015)
Container vessels have a challenging structural design with respect to fatigue; they are long and slender and have large openings in the deck. Their structural design in combination with high wave loads, makes these ships sensitive to fatigue damage. Classification societies mainly base their assumptions in the fatigue rules on elastic material response and the fatigue analysis is carried out using the stress-based approach. However, for harsh sea states the assumption of elastic material response is not fulfilled in local details where the stress concentration is high; cyclic plasticity may occur, which requires a strain-based fatigue assessment. The objective of this study is to present a methodology which combines the softwares Sesam and Abaqus to enable realistic hydrodynamic, structure and fatigue analyses of a container vessel in a harsh sea state. Both of the softwares are needed in order to be able to choose a solver in the structure analysis to be either linear or nonlinear, depending on the cyclic elastic or plastic material response. Analyses of a case study of a 4400 TEU (twenty-foot equivalent unit) container vessel on the North Atlantic route are presented. A long-term fatigue analysis is performed in order to search for the fatigue-critical locations in the ship. A part of the side-shell structure was chosen for a detailed study comparing results from a linear and nonlinear finite element analysis for two significant wave heights: 6.0 and 7.5m. The results show that for both of these wave heights cyclic plasticity occurs locally, but at a very low accumulation rate, which eventually results in elastic shakedown material response. Hence, the overall conclusion is that, in the studied location, a strain-based approach to fatigue is not necessary.